1984
DOI: 10.1037/h0085982
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical intention strategies: A review of rationales.

Linda Riebel

Abstract: This article summarizes contributions to the paradoxical perspective made by psychoanalysts, family therapists, logotherapists, Adlerian, and Morita therapists. In the analysis, six categories of rationales offered by these writers are deduced: overcoming resistance, disturbing systems, altering client perspectives, reversing excessive effort, learning theory, and intrapsychic factors such as disorientation or reframing. Attention is drawn to the fact that no information from clients is presented to substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Based on different clinical psychological theories (e.g., Frankl, ; Miller & Rollnick, ; Riebel, ; Watzlawick et al., ), as well as on the classic debating technique, reductio ad absurdum (Rescher, ), we define paradoxical thinking as a method of using a new nonjudgmental message(s) that is consistent with held attitudes and beliefs, i.e., falls within the message recipient's latitude of acceptance, but is provided in an amplified, exaggerated or even absurd manner. It is meant to elicit surprise, or a sense of absurdity regarding the held attitudes or the current situation, and will be especially effective among those who would normally be the most resistant.…”
Section: Paradoxical Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on different clinical psychological theories (e.g., Frankl, ; Miller & Rollnick, ; Riebel, ; Watzlawick et al., ), as well as on the classic debating technique, reductio ad absurdum (Rescher, ), we define paradoxical thinking as a method of using a new nonjudgmental message(s) that is consistent with held attitudes and beliefs, i.e., falls within the message recipient's latitude of acceptance, but is provided in an amplified, exaggerated or even absurd manner. It is meant to elicit surprise, or a sense of absurdity regarding the held attitudes or the current situation, and will be especially effective among those who would normally be the most resistant.…”
Section: Paradoxical Thinkingmentioning
confidence: 99%
“…Most of the early evidence of the effectiveness of paradoxical thinking interventions comes from the clinical psychological literature. This work (e.g., Frankl, ; Miller & Rollnick, ; Watzlawick et al., ; for a review see Riebel, ) suggest that individuals who are provided with amplified or exaggerated information or instructions that are in line with their held beliefs, attitudes, or behavior may change these beliefs, even when they are extremely negative and well entrenched. Using a similar line of thought, Frankl () advised his patients that, instead of avoiding the fear‐arousing stimulus, to think about very fearful cases, or in his words, “to do, or wish to happen, the very things [they fear]” (Frankl, , p. 227).…”
Section: Paradoxical Thinkingmentioning
confidence: 99%
“…This practice means that if "withdrawing" were to be relabeled "taking care of oneself," and "controlling" were to become "structuring one's environment," clients would often be better motivated to alter current maladaptive behavior (Weeks & L'Abate, 1982). The various rationales and strategies underlying paradoxical approaches have been reviewed by Riebel (1984). Again, empirical studies have yielded mixed results: Feldman et al (1982) found that paradoxical interpretation yielded more symptom remission than directives did, but findings by Lopez & Wambach (1982) were less conclusive.…”
Section: Therapists' Use Of Languagementioning
confidence: 99%
“…As interest in paradoxical techniques has steadily grown over the last several years, they have received increasing attention in the professional literature, with most of this attention being aimed at describing paradoxical techniques and what makes them work (Cade, 1984;Driscoll, 1985;Kercher & Smith, 1985;O'Connell, 1983;Omer, 1981;Riebel, 1984;Zeig, 1980). In addition to this descriptive/explanatory body of literature on paradox, there has also been a slowly accumulating body of experimental outcome studies.…”
mentioning
confidence: 99%